Traditional and biomedical health practices of adolescent boys and young men living with perinatally-acquired HIV in the Eastern Cape Province of South Africa - Lesley Gittings; Christopher Colvin; Rebecca Hodes (Taylor & Francis Group, 2023)
Men are less vulnerable to HIV acquisition than women, but have poorer HIV-related health outcomes. They access HIV services less, and are more likely to die on antiretroviral therapy. The adolescent epidemic presents further challenges, and AIDS-related illness is the leading cause of death among adolescents in sub-Saharan Africa. We explored the health practices of adolescent boys and young men (aged 13-22) living with perinatally-acquired HIV and the processes through which these practices are formed and sustained. We engaged health-focused life history narratives (n = 35), semi-structured interviews (n = 32) and analysis of health facility files (n = 41), alongside semi-structured interviews with traditional and biomedical health practitioners (n = 14) in the Eastern Cape, South Africa. Participants did not access traditional products and services for HIV, a finding that deviates from much of the literature. Findings suggest that health practices are mediated not only by gender and culture, but also childhood experiences of growing up deeply embedded in the biomedical health system.